2016
DOI: 10.1074/jbc.m116.729103
|View full text |Cite
|
Sign up to set email alerts
|

The Tat Substrate CueO Is Transported in an Incomplete Folding State

Abstract: In Escherichia coli, cytoplasmic copper ions are toxic to cells even at the lowest concentrations. As a defense strategy, the cuprous oxidase CueO is secreted into the periplasm to oxidize the more membrane-permeable and toxic Cu(I) before it can enter the cytoplasm. CueO itself is a multicopper oxidase that requires copper for activity. Because it is transported by the twin-arginine translocation (Tat) pathway, which transports folded proteins, a requirement for cofactor assembly before translocation has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…In vitro translocation assays were carried out as described previously (60). As translocation substrate served a T61C variant of the HiPIP precursor, which was fluorescence-labeled by modification of the cysteine with fluorescein-5-maleimide using standard protocols for maleimidecoupling (61).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro translocation assays were carried out as described previously (60). As translocation substrate served a T61C variant of the HiPIP precursor, which was fluorescence-labeled by modification of the cysteine with fluorescein-5-maleimide using standard protocols for maleimidecoupling (61).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the twin‐arginine translocation (Tat) system is required for copper resistance in P. syringae DC3000 (Bronstein et al ., ). The Tat system transports folded proteins from the cytoplasm to the periplasm and has been associated with the transport of multi copper oxidases to the periplasm in gram‐negative bacteria (Bronstein et al ., ; Rowland and Niederweis, ; Stolle et al ., ). Our experiments identified the tatB homologue BCAL0324 as a copper resistance gene.…”
Section: Resultsmentioning
confidence: 97%
“…For example, it was shown that several disulphide-bonded proteins (including human growth hormone, a single-chain variable fragment (scFv) and interferon α2β) can be exported in the reduced state in wild type cells [23] and the native Tat substrate CueO is exported in its apo form [24]. However, these proteins are believed to adopt near-native structures even in the absence of disulphide bond formation or Cu ligation, and so the extent of misfolding is likely to be minimal.…”
Section: Accepted Manuscriptmentioning
confidence: 99%